Low temperature micro solid oxide fuel cells with proton-conducting ceramic electrolytes - Li, Yong (2016)
Solid oxide fuel cells (SOFCs) are highly efficient energy conversion devices which can convert chemical energy directly into electricity without combustion. The major hurdle to SOFCs is the requirement of high operating temperature (>800 °C), which leads to a technological challenge for materials development and thermal management. Thus reducing the operating temperature of SOFCs to intermediate temperature (500-800 °C) range or even low temperature range (<500 °C) would greatly benefit the wide application of SOFC technology. Reducing the electrolyte thickness and/or utilizing proton-conducting electrolytes are two efficient approaches to reduce the operating temperature of SOFCs, as well as maintain high output power density. This work is dedicated to achieve high performance SOFCs at low operating temperature of 300-500 °C by using micro-SOFCs (µ-SOFCs) with proton-conducting thin film electrolytes.